Findbuch des Bestandes Abt. 8.3 Schleswig-Holstein-Gottorfisches (Großfürstliches) General-Landes- und Ökonomie-Verbesserungsdirektorium zu Kiel 1766-1807 - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2019)
In the second half of the 18th century, profound reforms in the agricultural sector had a decisive impact on the economic and social development in the duchies of Schleswig and Holstein. On June 19th, 1766, the grand ducal Government of Gottorf established the General State and Economic Improvement Directorate ("General-Landes- und Ökonomie-Verbesserungsdirektorium") in Kiel to implement the agricultural reform measures in the Gottorf shares of the Duchy of Holstein. The primary tasks of the General Directorate included the surveying and distribution of the village estates, the resulting reorganisation of the services and duties of the subjects and the parcelling out of the domains and outlying buildings. The General State Visitation Commission ("Generallandesvisitationskommission") was associated with the General Directorate. Every second year the Commission was to carry out a comprehensive country search in order to obtain a thorough picture of the conditions in the individual administrative districts. Furthermore, the Commission had to check compliance with the ordinances in the area of competence of the General Directorate. The files of the General Directorate were handed over to the Land Commission in June 1808. In order to facilitate the use of the important information for questions on regional and local agricultural, economic and social history, but also for field name research, the holdings were completely reviewed in 2014 and included in the archival database. Here the data of the old finding aids on titles and running times of all archival records in the holdings were checked. The proven order of the holdings served as the basis for the revision and only underwent minor changes.